Comparison of efficacy three-site versus single-site steroid injections for the treatment of adhesive capsulitis. (July 2022) - Sharif, Muhammad; Khan, Muhammad Sufyan; Ahmed, Tayyeba Khursheed; Aziz, Wajahat; Rasheed, Uzma; Zammurrad, Shazia; Iqbal, Arslan; Mumtaz, Hassan; Hussain, Hassan ul; Hasan, Mohammad; Erum, Sheeza
Abstract: Background: Frozen shoulder or adhesion capsulitis is a frequent ailment that causes pain and progressively restricts both active and passive shoulder motions. It is estimated that it affects 2%–5% of the general population and up to 20% of diabetes mellitus patients. We aimed to compare the effectiveness of three-site steroid injections against one-site injections in the treatment of adhesive capsulitis. Methodology: The Rheumatology Department of Pakistan Institute of Medical Sciences in Islamabad conducted this cross-sectional study. Between August 2021 to December 2021. The study comprised a total of 98 patients. This study included patients of both genders with shoulder pain between the ages of 40 and 70. Patients were divided into two groups & dosage was given at Sub-coracoid, Subacromial, and Posterior Capsule.The CONSTANT score was used to assess patients three times (Initial, 3months & 6 months later). Results: The average age, gender distribution, and dominant/non-dominant side ratio of the participants were nearly identical between the two groups. More patients in group B (77.22 8.17) had a higher mean CONSTANT score than those in group A (72.73 7.05). Patients were checked in on again after three and six months. Conclusion: The three-site injection technique is a safe and effective method for frozen shoulder. It provides an early recovery and improved shoulder function with a reduced frequency of relapse as compared to single-site injection techniques. Highlights: Adhesive capsulitis can be treated effectively with Three site injection technique. Patients with Three site injection technique have improved quality of life. Patients with single-site injections have more chances of relapse.